Analisis Biaya Transportasi dalam Pendistribusian Singkong Menggunakan Metode Northwest Corner dan Least Cost - Atikah Atikah; Tiara Tiara; Surya Perdana (eCo-Fin, 2024)
Transportation plays an important role in supply chain management, where transportation is the process of determining how and when goods should be delivered to consumers. In the transportation method used, it is necessary to consider efficiency and speed in delivering goods. The object of this research is cassava plantations, which are in the Bogor district, especially in the Jonggol, Cariu and Sukamakmur sub-districts. The harvest from this plantation is allocated to 3 factory areas in the Bekasi district. The problem faced is the high transportation costs in allocating the harvest. So, the minimum distribution costs that will be incurred in allocating the harvest to various chip factories are not yet known, and the route and quantity of cassava that will be sent is not yet known. One method of transportation is the Northwest Corner (NWC) and Least Cost Method. The Northwest Corner and Least Cost methods are used in determining goods delivery routes, so that you can calculate the lowest transportation costs from one place to another. Based on the research results, the minimum distribution cost allocated for cassava is IDR 5,410,000.00 with distribution channels namely Cariu to Muktijaya as much as 90 tons, Sukamakmur to Cijengkol as much as 100 tons, Cariu to Ciledug as much as 10 tons, Jonggol to Ciledug as much as 140 tons, and Sukamakmur to Ciledug as much as 20 tons.